Rebelde Mexicano: A relação do fã com o uniforme do Elite Way School - Mesquita, Ariágila Matos (2021)
The work involves issues such as imitation, belonging, social groups and consumption symbolic, in order to understand the relationship of the fan with the uniforms used as costumes in the Mexican telenovela Rebelde, shown in Brazil in 2005. Through bibliographical and qualitative research, in the form of interviews with fans of the band RBD from Fortaleza, Ceará, aged between 22 and 30 years old. Thus, it was possible to conclude that the Elite Way School uniforms, works for fans as a physical representation of a broader concept, which is directly linked to the concepts of Rebelde and RBD, present in the fan's subjectivity.